2022
DOI: 10.3390/su14105817
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Hazards and the Associated Impacts on Households’ Willingness to Adopt Water-Saving Measures: Evidence from Mexico

Abstract: Numerous regions across the globe are facing water shortage challenges, and domestic water demands are predicted to grow vastly by 2050. In this regard, household water-saving measures are critical to adapt to future risks. Few studies have evaluated the association between climate change-related threats and their impacts on water-saving activities and intentions. However, a limitation in this line of research is the assumption that only the hazards that directly affect water shortages, such as drought, can in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…One of the worst catastrophes of recent years that hit the state was the drought that started in 2011 and ended with hurricane Ingrid in 2013, which was the second most severe in history, only surpassed by one in the 1950s [51]. In the summer of 2022, a one-day water supply cutoff was implemented for each MMA sector, posing a challenge for millions of people to receive water [52]. Additionally, water pressure control, which began in July 2022, was still in operation for the summer of 2023 [53].…”
Section: Monterrey Mexicomentioning
confidence: 99%
See 1 more Smart Citation
“…One of the worst catastrophes of recent years that hit the state was the drought that started in 2011 and ended with hurricane Ingrid in 2013, which was the second most severe in history, only surpassed by one in the 1950s [51]. In the summer of 2022, a one-day water supply cutoff was implemented for each MMA sector, posing a challenge for millions of people to receive water [52]. Additionally, water pressure control, which began in July 2022, was still in operation for the summer of 2023 [53].…”
Section: Monterrey Mexicomentioning
confidence: 99%
“…The significance of these aspects is directly highlighted in the most well-known WS definitions, such as the one from the UN, through pointing out the "sustainable access to adequate quantities of acceptable quality water" [3]. It is therefore of high importance for both cities to have adequate WS/GI management methods to address quantitative/qualitative aspects of WS, as Monterrey is facing clean water shortages [52] and Brussels needs to deal with possible drought and high water stress challenges [30,67].…”
Section: Water-security Aspectsmentioning
confidence: 99%
“…People living in rural areas who rely on agriculture and livestock for their livelihoods are particularly vulnerable as they are dependent on natural resources 12 . Recent studies show that exposure to climate shocks is connected with climate change risk perception and willingness to change behaviors 13 , 14 . One study conducted in Mexico found that younger people were significantly more willing to take on adaptation measures aimed at conserving water 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that exposure to climate shocks is connected with climate change risk perception and willingness to change behaviors 13 , 14 . One study conducted in Mexico found that younger people were significantly more willing to take on adaptation measures aimed at conserving water 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation